Pengaruh Penggunaan Podcast Youtube Podcastacular Terhadap Minat Belajar Siswa (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effect of using the YouTube podcast Podcastacular on students' learning interest at SMA Negeri 3 Semarang. The study used a quantitative approach with a pre-experimental design in the form of a One Group Pretest–Posttest Design. The research subjects were 36 grade XII students selected using a saturated sampling technique. Data collection was carried out through a Likert scale questionnaire that had been tested for validity and reliability. Data analysis used a normality test to determine the distribution of the data, a paired sample t-test to test the difference in the average pretest and posttest scores on normally distributed data, and a Wilcoxon test as a nonparametric test to strengthen the results of the data difference test. The results showed that the data were normally distributed with a significance value > 0.05. The results of the paired sample t-test obtained a significance value of 0.019 (